Comparison of the Effectiveness of Psychological Debriefing–Based Intervention and Schema Therapy on Post-Traumatic Stress Arousal Symptoms and Coping Styles in Adolescent Girls Affected by Sexual Abuse - Azizi, Marzieh; Aghdasi, Alinaghi; Agdamibaher, Alireza; Mesrabadi, Javad (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2025)
Objective: This study aimed to compare the effectiveness of psychological debriefing and schema therapy on post-traumatic stress arousal symptoms and coping styles among adolescent girls affected by sexual abuse. Methods and Materials: This quasi-experimental study employed a pretest–posttest control group design with three groups: psychological debriefing, schema therapy, and control. The sample included 45 adolescent girls aged 12–18 years who were referred to the Social Emergency Center in Varamin, Iran, in 2024, after experiencing sexual abuse. Participants were selected through purposive sampling based on inclusion criteria and randomly assigned to one of the three groups (15 per group). The interventions consisted of a 12-session schema therapy program based on Young’s model and a single-session (two-hour) psychological debriefing protocol based on Mitchell and Everly’s model. Research instruments included the Endler and Parker Coping Inventory for Stressful Situations (CISS) and the PTSD Symptom Scale developed by Weathers et al. Data were analyzed using mixed-design analysis of variance (ANOVA) with a significance level of p < .05. Findings: The results showed that both interventions led to a significant increase in problem-focused coping and a significant reduction in emotion-focused and avoidance coping styles, as well as decreased emotional arousal symptoms among adolescent girls in the experimental groups compared to the control group (p < .05). The within-group and interaction effects of time and group were statistically significant, while no significant differences were observed between the two intervention groups, indicating comparable efficacy of psychological debriefing and schema therapy in reducing post-traumatic symptoms. Conclusion: Both schema therapy and psychological debriefing are effective trauma-focused interventions for adolescent girls affected by sexual abuse, improving coping strategies and reducing hyperarousal symptoms. Integrating these methods into a staged treatment protocol may optimize recovery outcomes for this vulnerable population.